ANALYSIS OF ELECTRONIC WASTE DISPOSAL PROBLEMS - Dzierkalis, Mārtiņš; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Electronic waste and the problems of disposal thereof are analyzed in this research paper. In research was used theoretical analysis method on the basis of nowadays achievements in this field and empirical– instrumental method . Recommendations to prevent problems of disposal of electronic waste are provided.